2019
DOI: 10.1002/cam4.2652
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world efficacy and potential mechanism of resistance of icotinib in Asian advanced non‐small cell lung cancer with EGFR uncommon mutations: A multi‐center study

Abstract: The response to icotinib in advanced non‐small cell lung cancers (NSCLC) with EGFR uncommon mutation (EGFRum) is unclear. Here we reported the efficacy and potential resistance mechanism of icotinib in Chinese EGFRum NSCLC patients. Between July 2013 and November 2016, 3117 NSCLC patients were screened for EGFRum in a multi‐center study in China. Circulating tumor DNA (ctDNA) was detected and analyzed using next‐generation sequencing (NGS) after progression from icotinib. The efficacy, safety and the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Other several resistance mechanisms to icotinib in NSCLC harboring uncommon mutations include EGFR extracellular domain mutation, BCL2L11 loss, MET amplification, ERBB2 amplification, MYC amplification, PTEN mutation, and PIK3CA mutation. 18,37 In this study, apart from one patient with L858R mutation, one patient with L833V/H835L was detected with a secondary T790M mutation. This secondary drug resistance mechanism is consistent with a previous case report.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Other several resistance mechanisms to icotinib in NSCLC harboring uncommon mutations include EGFR extracellular domain mutation, BCL2L11 loss, MET amplification, ERBB2 amplification, MYC amplification, PTEN mutation, and PIK3CA mutation. 18,37 In this study, apart from one patient with L858R mutation, one patient with L833V/H835L was detected with a secondary T790M mutation. This secondary drug resistance mechanism is consistent with a previous case report.…”
Section: Discussionmentioning
confidence: 54%
“…~93% are present in the first four exons (18)(19)(20)(21) of the gene encoding tyrosine kinase domain, including exon 18 Gly719Xaa (G719X) (~3%), exon 21 Leu861Gln (L861Q) (~1%), and exon 20 Ser768Ile (S768I) mutations (~1%), as well as other insertions in exon 19 or 20 (ins19; 0.6%, and ins20; ~6%). 10 Although at low frequency, approximately tens of thousands of new cases worldwide are reported each year because of the large population base of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers analyzed the clinical data from the NEJ002 study involving 10 participants harboring uncommon mutations, and the results showed that gefitinib was ineffective against G719X or L861Q mutation (13). In contrast, several retrospective studies observed moderate efficacy of firstgeneration EGFR-TKIs against uncommon mutations, with ORR ranging from 13.27% to 48.40%, and mPFS ranging from 5.0 to 7.7 months (8,14,15). Meanwhile, increasing evidence has suggested improved efficacy of second-generation EGFR-TKIs on patients with uncommon mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, increasing studies are conducted on tumor resistance through CTC. Scholars study choriocarcinoma [ 22 ], colorectal cancer [ 23 26 ], liver cancer [ 27 ], lung cancer [ 28 , 29 ], breast cancer [ 30 , 31 ], lymphoma [ 32 ], gastric cancer [ 33 ] and other malignant tumors through CTC to explore the drug resistance of tumor cells. However, most current CTC analyses are based on CTC epithelial biomarkers, and epithelial biomarkers may not be expressed in several tumor types [ 34 ].…”
Section: Single-cell Sequencing Of Ctc and Drug Resistancementioning
confidence: 99%